Working Load Characteristics of the PDC-Cone Composite Bit under Impact and Scraping - Kuilin Huang; Chunxiao Zhou; Yingxin Yang; Haitao Ren; Qingzhi Niu (Shock and Vibration)
The PDC-roller hybrid bit combines the cutting structure of a tricone bit with a PDC bit. It can achieve good results, breaking rock in directional drilling, drilling in inhomogeneous formations, and drilling in formations with high levels of hardness, and it can achieve the engineering goals of increasing speed and efficiency. First, we analyzed the rock-breaking mechanism of the composite bit and the principles of cushioning, torsion reduction, and prebreaking of the cone teeth during the breaking of rock. Second, cutting load models of the cone teeth and PDC teeth were established through unit experiments and through the calculation methods of the axial force, lateral force and torque, and lateral bending moment of the composite bit. Third, the digital simulation and analysis system was improved to include the function of calculating the working load of the composite bit. Taking an 8-1/2 inch, 2 + 4 type composite bit as an example, the working load characteristics of three cutting structures (cone, blade, and composite) were analyzed and compared. The analysis shows that the composite bit has high drilling efficiency, obvious deviation advantages, and good working stability under specific formation conditions. This paper provides technical support for the performance analysis, formation adaptability evaluation, and cutting structure design optimization of the PDC-cone bit.